PENGARUH LITERASI KEUANGAN DAN PERSEPSI RISIKO TERHADAP MINAT INVESTASI TABUNGAN EMAS PEGADAIAN SYARIAH: The Influence of Financial Literacy and Risk Perception on Interest in Sharia Pawnshop Gold Savings Investment - Rafikah, Syarifah (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to determine the influence of financial literacy and risk perception on investment interest in gold savings among customers of Pegadaian Syariah Hasanuddin Gowa Branch. The background of this study is the low level of financial literacy and risk perception in the community, resulting in suboptimal investment decisions, particularly in gold savings products that have the potential for stability and inflation resistance. The research method used a quantitative approach with data collection through questionnaires from 79 respondents using purposive sampling. Data analysis was performed using multiple linear regression to test the influence of variables partially and simultaneosly The results showed that financial literacy had a positive and significant effect on investment interest in gold savings, with a regression coefficient of 0.566 and a significance level of 0.000 <0.05. Risk perception also had a positive and significant effect, with a regression coefficient of 6.592 and a significance level of 0.000 < 0.05. Simultaneously, financial literacy and risk perception significantly influenced gold savings investment interest, with a calculated F of 132.413 > Ftable of 3.117 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.777 indicates that 77.7% of the variation in gold savings investment interest is explained by these two variables.